Amino Acids Are an Ineffective Fertilizer for Dunaliella spp. Growth - Murphree, Colin A.; Dums, Jacob T.; Jain, Siddharth K.; Zhao, Chengsong; Young, Danielle Y.; Khoshnoodi, Nicole; Tikunov, Andrey; Macdonald, Jeffrey; Pilot, Guillaume; Sederoff, Heike (Frontiers in Plant Science, 2017)
Autotrophic microalgae are a promising bioproducts platform. However, the fundamental requirements these organisms have for nitrogen fertilizer severely limit the impact and scale of their cultivation. As an alternative to inorganic fertilizers, we investigated the possibility of using amino acids from deconstructed biomass as a nitrogen source in the genus Dunaliella. We found that only four amino acids (glutamine, histidine, cysteine, and tryptophan) rescue Dunaliella spp. growth in nitrogen depleted media, and that supplementation of these amino acids altered the metabolic profile of Dunaliella spp. cells. Our investigations revealed that histidine is transported across the cell membrane, and that glutamine and cysteine are not transported. Rather, glutamine, cysteine, and tryptophan are degraded in solution by a set of oxidative chemical reactions, releasing ammonium that in turn supports growth. Utilization of biomass-derived amino acids is therefore not a suitable option unless additional amino acid nitrogen uptake is enabled through genetic modifications of these algae.